Challenges and Opportunities in Clinical Diagnostic Routine of Envenomation Using Blood Plasma Proteomics - Cavalcante, Joeliton dos Santos [UNESP]; de Almeida, Denis Emanuel Garcia [UNESP]; Moraes, Micael Saggion [UNESP]; Santos, Sophia Ribeiro [UNESP]; Pincinato, Pedro Moriel [UNESP]; Riciopo, Pedro Marques [UNESP]; de Oliveira, Laís Lacerda B.; Monteiro, Wuelton Marcelo; Ferreira-Junior, Rui Seabra [UNESP] (MDPI, 2023)
Specific and sensitive tools for the diagnosis and monitoring of accidents by venomous animals are urgently needed. Several diagnostic and monitoring assays have been developed; however, they have not yet reached the clinic. This has resulted in late diagnoses, which represents one of the main causes of progression from mild to severe disease. Human blood is a protein-rich biological fluid that is routinely collected in hospital settings for diagnostic purposes, which can translate research progress from the laboratory to the clinic. Although it is a limited view, blood plasma proteins provide information about the clinical picture of envenomation. Proteome disturbances in response to envenomation by venomous animals have been identified, allowing mass spectrometry (MS)-based plasma proteomics to emerge as a tool in a range of clinical diagnostics and disease management that can be applied to cases of venomous animal envenomation. Here, we provide a review of the state of the art on routine laboratory diagnoses of envenomation by snakes, scorpions, bees, and spiders, as well as a review of the diagnostic methods and the challenges encountered. We present the state of the art on clinical proteomics as the standardization of procedures to be performed within and between research laboratories, favoring a more excellent peptide coverage of candidate proteins for biomarkers. Therefore, the selection of a sample type and method of preparation should be very specific and based on the discovery of biomarkers in specific approaches. However, the sample collection protocol (e.g., collection tube type) and the processing procedure of the sample (e.g., clotting temperature, time allowed for clotting, and anticoagulant used) are equally important to eliminate any bias.
Keywords: biomarkers; blood plasma; clinical proteomics; human envenoming